Factor VIII with a 237 amino acid B‐domain has an extended half‐life in F8‐knockout mice. (25th January 2019) - Bloem, E.; Karpf, D. M.; Nørby, P. L.; Johansen, P. B.; Loftager, M.; Rahbek‐Nielsen, H.; Petersen, H. H.; Blouse, G. E.; Thim, L.; Kjalke, M.; Bolt, G.
Abstract : Essentials Factor (F)VIII with an intermediate‐length B‐domain showed higher levels in murine gene therapy. FVIII with different B‐domain lengths were analysed. FVIII variants with B‐domains between 186 and 240 amino acids (aa) have extended half‐life in mice. Reduced cell binding of FVIII with a 237aa B‐domain may explain the extended half‐life. Summary: Background: Factor VIII consists of the A1‐domain, A2‐domain, B‐domain, A3‐domain, C1‐domain, and C2‐domain. FVIII with an intermediate‐length B‐domain of 226 amino acids (aa) has previously been evaluated in murine gene therapy studies. Objective: To characterize FVIII with intermediate‐length B‐domains in vitro and in vivo in F8‐ knockout (KO) mice. Methods and results: FVIII molecules with B‐domains of 186–240aa had longer half‐lives in F8 ‐KO mice than FVIII molecules with shorter or longer B‐domains. FVIII with a B‐domain containing the 225 N‐terminal aa fused to the 12 C‐terminal aa of the wild‐type B‐domain (FVIII‐237) had a 1.6‐fold extended half‐life in F8 ‐KO mice as compared with FVIII with a 21aa B‐domain (FVIII‐21). The in vitro and in vivo activity of FVIII‐237 were comparable to those of FVIII‐21, as was binding to von Willebrand factor. Cell binding to LDL receptor‐related protein 1 (LRP‐1)‐expressing cells was markedly reduced for FVIII‐237 as compared with FVIII‐21, whereas the affinity for LRP‐1 was not reduced in surface plasmon resonance (SPR) studies. FVIII‐21 cell binding and internalization could be inhibited by a fragment consisting of the 226 N‐terminal aa of the FVIII B‐domain, and SPR analysis suggested that this B‐domain fragment might bind with weak affinity to FVIII‐21. Conclusion: Reduced cell binding of FVIII‐237 might explain the observed extended half‐life in F8 ‐KO mice. This may contribute to the increased FVIII levels measured in murine gene therapy studies using FVIII constructs with similar B‐domain lengths.